Electrical Characteristics of Vertical Ni/β-Ga2O3 Schottky Barrier Diodes at High Temperatures. (21st September 2016) - Oh, Sooyeoun; Yang, Gwangseok; Kim, Jihyun
Abstract : Vertical geometry β-Ga2 O3 Schottky barrier diodes (SBDs) were fabricated and the rectifying forward and reverse current-voltage characteristics were demonstrated at elevated temperatures for a freestanding β-Ga2 O3 material with an ultra-wide bandgap of ∼4.9 eV. The breakdown voltage of the fabricated β-Ga2 O3 SBDs with a punch-through configuration was ∼210 V without the edge-termination method. The electrical field and potential distributions were numerically simulated with a finite element method. The on-resistance was 2582 Ω·cm 2 at 25°C, and decreased to 0.043 Ω·cm 2 at 225°C. The figure-of-merit ( V BR 2 / R on ) was approximately 17.1 W·cm −2 . The temperature-dependent Schottky barrier height and ideality factor were also determined. The developed β-Ga2 O3 SBDs with the punch-through structure exhibit great potential for high power and high temperature applications.